Hubungan Kebiasaan Olahraga Aerobik Terhadap Dismenore Primer pada Mahasiswi 18-24 Tahun Fakultas Kedokteran Universitas Udayana - Sutawinata, Agung Ary; Dwi Primayanti, Dewa Ayu Inten (E-Jurnal Medika Udayana; Vol 6 No 12 (2017): E-Jurnal Medika Udayana, 2017)
Some research have been done on the last two decades. The result showed correlation of exercise and primary dysmenorrhea significantly reduce pain caused by symptoms arising and reduce drug use, but did not reduce bleeding out. The purpose of this research is to find out the relationship between aerobic exercise habit with primary dysmenorrhea in female medical students of Faculty of medicine 2016 age 18-24 years. The design of the research is a descriptive research analytical method with cross sectional approach. The sample in this study are women ages 18-24 years at the medical faculty Udayana University 2016 Generation of 2013 with a total of 96 respondents obtained via simple random sampling techniques, namely the sampling technique in which every Member or unit of the population gets the same opportunity for selected as samples. This research use instrument in the form of a detailed questionnaire for both variables, good habits of primary dysmenorrhea or exercise. The Results of the statistical tests by using test chi square value of the significance of p = 0,05. On the suggestion term of sport and incidence of dysmenorrhea retrieved value p<0,05 (p < a). Concludes there is a meaningful relationship between the duration of aerobic exercise with primary dysmenorrhea wuith p<0,05. Keyword : Primary Dysmenorrhea, Aerobic Exercise, type of exercise , Exercise Frequency , Exercise Duration Frequency